2010
DOI: 10.1007/s10236-009-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of storm surge/tide predictions between a 2-D operational forecast system, the regional tide/storm surge model (RTSM), and the 3-D regional ocean modeling system (ROMS)

Abstract: In this study, we compare simulated storm surges run on the two-dimensional operational storm surge/tide forecast system (regional tide/storm surge model (RTSM), based on Princeton ocean model) of the Korean Meteorological Administration and the three-dimensional regional ocean modeling system (ROMS), using observational data from 30 coastal tidal stations of three typhoons that struck Korea in 2007. A maximum positive bias of 6.8 cm was found for Typhoon Manyi predicted by ROMS, while a maximum negative bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Numerous numerical models have been developed and applied to simulate hurricane/typhoon-induced storm surges [6][7][8][9][10][11][12][13][14]. Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous numerical models have been developed and applied to simulate hurricane/typhoon-induced storm surges [6][7][8][9][10][11][12][13][14]. Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The fully nonlinear Finite Volume Coastal Ocean Model (FVCOM) with a high-resolution unstructured mesh was implemented to study the storm surge due to Hurricane Ike along the Texas-Louisiana coast (Rego and Li 2010). You et al (2010) compared the storm surge outputted by POM and Regional Ocean Modeling System (ROMS) by taking the cases of three typhoons that struck Korea in 2007. Several authors including Higaki and Hayashibara (2008) and Higaki et al (2009) have described the JMA (Japan Meteorological Agency) storm surge model which includes the parametric wind model (Fujita 1952) and non-hydrostatic model (Saito et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rego and Li (2010) studied the storm surge of Hurricane Ike along the Texas-Louisiana coast using the fully nonlinear Finite Volume Coastal Ocean Model (FV-COM) with a high-resolution unstructured mesh. You et al (2010) compared simulated storm surges using the twodimensional operational storm surge/tide forecast system (region tide/storm surge model, RTSM, which is based on the Princeton Ocean Model), and the three-dimensional regional ocean modeling system (ROMS) using the observed data from 30 coastal tidal stations from three typhoons that struck Korea in 2007.…”
Section: Introductionmentioning
confidence: 99%